Genetic study of congenital bile-duct dilatation identifies de novo and inherited variants in functionally related genes. Issue 1 (December 2016) - Wong, John; Campbell, Desmond; Ngo, Ngoc; Yeung, Fanny; Cheng, Guo; Tang, Clara; Chung, Patrick; Tran, Ngoc; So, Man-ting; Cherny, Stacey; Sham, Pak; Tam, Paul; et al.
Abstract Background Congenital dilatation of the bile-duct (CDD) is a rare, mostly sporadic, disorder that results in bile retention with severe associated complications. CDD affects mainly Asians. To our knowledge, no genetic study has ever been conducted. Methods We aim to identify genetic risk factors by a "trio-based" exome-sequencing approach, whereby 31 CDD probands and their unaffected parents were exome-sequenced. Seven-hundred controls from the local population were used to detect gene-sets significantly enriched with rare variants in CDD patients. Results Twenty-one predicted damaging de novo variants (DNVs; 4 protein truncating and 17 missense) were identified in several evolutionarily constrained genes (p < 0.01). Six genes carrying DNVs were associated with human developmental disorders involving epithelial, connective or bone morphologies (PXDN, RTEL1, ANKRD11, MAP2K1, CYLD, ACAN) and four linked with cholangio- and hepatocellular carcinomas(PIK3CA, TLN1 CYLD, MAP2K1) . Importantly, CDD patients have an excess of DNVs in cancer-related genes (p < 0.025). Thirteen genes were recurrently mutated at different sites, forming compound heterozygotes or functionally related complexes within patients. Conclusions Our data supports a strong genetic basis for CDD and show that CDD is not only genetically heterogeneous but also non-monogenic, requiring mutations in more than one genes for the disease to develop. The data is consistent with the rarity and sporadic presentation of CDD.